KUALITAS CORPORATE GOVERNANCE PERBANKAN SYARIAH DITINJAU DARI PERSPEKTIF KINERJA PERUSAHAAN - Purwaningsih, Septi (Perwira Journal of Economics & Business, 2024)
This research was a quantitative descriptive study that aims to measure the effect of Islamic banking performance using the Maqashid Syariah Index Method. The population in this study were all Islamic Commercial Banks listed on the Indonesia Stock Exchange from 2016-2018, that was 14 banks consisting of Aceh Syariah Bank, Bukopin Syariah Bank, Jabar Banten Syariah Bank, Mega Syariah Bank, Muamalat Bank, NTB Syariah Bank, Syariah Mandiri Bank, Victoria Syariah Bank, BCA Syariah, BNI Syariah, BRI Syariah, BTPN Syariah, Maybank Syariah, and Panin Syariah Bank. This research used purposive sampling technique. The data collection technique used was documentation. The data analysis technique in this study used multiple linear regression analysis with SPSS 22 software. The results showed that the background of the syariah supervisory board, the number of audit committee members, Islamic Social Responsibility, affected on the performance of Islamic banking, while the results of the research on Islamic Corporate Identity variables did not affect the performance of Islamic banking which was assessed using the Maqashid Syariah Index Method. The implication of this research is expected to increase literacy regarding the performance of Islamic banking which is reviewed using the Maqashid Syariah Index Method and also as input for stakeholders to pay more attention to the operating system to comply with Islamic law.